2020
DOI: 10.3991/ijet.v15i16.10540
|View full text |Cite
|
Sign up to set email alerts
|

Learning Algebra using Augmented Reality: A Preliminary Investigation on the Application of Photomath for Lower Secondary Education

Abstract: This study aims to determine the effect of Photomath mobile application on the achievement and attitude of learning algebraic equations for lower secondary school students in Malaysia. Photomath is a free mobile application, for both ios and android platforms, which uses computer vision and image understanding technology to scan math equations using the mobile camera to subsequently provide worked solutions. The application recognises equations of both printed and handwritten in nature and provides step-by-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 9 publications
2
30
0
2
Order By: Relevance
“…However, it is unclear whether the mobile application was used only for teaching or also for the assessment as well. A similar Malaysian study reported in [10] has also found improved performance in the case of algebraic equations. Mainly South American (Brazil, Peruvian, etc.)…”
Section: Literature Reviewsupporting
confidence: 65%
“…However, it is unclear whether the mobile application was used only for teaching or also for the assessment as well. A similar Malaysian study reported in [10] has also found improved performance in the case of algebraic equations. Mainly South American (Brazil, Peruvian, etc.)…”
Section: Literature Reviewsupporting
confidence: 65%
“…Therefore, utilising appropriate visualisation technology is also crucial to facilitate a student's spatial visualisation skills (Margulieux, 2020). Emerging technology such as virtual and augmented reality (Leonard & Fitzgerald, 2018;Saundarajan et al, 2020;Wahyu et al, 2020), interactive whiteboard (Wong et al, 2020) and other electronic media (Suparmi et al, 2020) allows students to attain more insight and comprehend greater information amount than the static images and information in textbooks. Students are inspired and able to grasp what the information reflects in a shorter period through viewing the information in the physical environment (Liu et al, 2020).…”
Section: Challenge 5: Lack Of Emphasis On Spatial Visualisation Capabilities In Educationmentioning
confidence: 99%
“…Penukaran bentuk am fungsi kuadratik kepada bentuk verteks merupakan unit yang terkandung dalam bab 2 Fungsi Kuadratik Matematik Tambahan Tingkatan 4 di bawah bidang Algebra. Algebra merupakan salah satu bidang matematik yang mentafsirkan makna dan tujuan dengan menggunakan pemboleh ubah dan menjadi komponen utama matematik yang meluas digunakan dalam disiplin matematik lain seperti aritmetik, geometri, statistik dan kalkulus (Saundarajan et al, 2020). Pemikiran dan pengetahuan algebra sangat penting dalam mentafsirkan masalah di sekeliling secara matematik untuk mencari jalan penyelesaian (Ling et al, 2019).…”
Section: Pengenalanunclassified